PENGARUH PENGELASAN FCAW TANPA DAN DENGAN PENAMBAHAN PANAS TERHADAP PERUBAHAN SIFAT MEKANIK DAN STRUKTUR MIKRO SAMBUNGAN LAS - Subeki, Nur; -, Jamasri; Ilman, M.N.; Iswanto, P.T. (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2015)
The Welding processes are delivery used joining steel, especially used in civil construction, piping and ship manufacturing. Many of the benefits that can be obtained from welded joint is the joining can be cheap, rapid manufacturing, varied shape and lighter construction. One of the welding techniques that is widely used for joining the steel construction is Flux Core Arc Welding (FCAW). The problem that found in welding joints is the tensile strength in welding area is low and uneven hardness in the weld joint. The aim of this research was to determine the mechanical properties of FCAW Welding process and find out micro structures formed by the addition of heat around the welding.In this research, FCAW welding has been divided into two groups; the ones group is manufacturing without addition of heating, and the second group is manufacturing by heating 200 Â°C. Every group of manufactures would be test by chemical compositions, macro photos, micro photos, tensile strength and hardness number. The results of this research shows that the addition of heat at 200 Â°C could be increase the yield strength and ultimate strength. The heating also could be very small impact on the change in the hardness of weld area, but it could be reduce the hardness in HAZ area significantly. Micro structure formed then the weld area has been dominated by acicular ferrite micro structure, grain boundary ferrite dominate in coarse HAZ, the pearlite and ferrite with grain aggrandizement take place in smooth HAZ and base metals.